Program promosi kesehatan dalam upaya mencegah pernikahan dini - Asnuddin Asnuddin; Andi Palla; Wilda Rezki Pratiwi (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2021)
The knowledge of early marriage practices and the health impacts among adolescent in a health promotion program Background: Adolescence is a period of human life that is very strategic, important and has a broad impact on subsequent developments.Marriage at an early age is prone to reproductive health problems and is prone to stress. Health education media such as videos can be used as a tool in providing health education. The use of video media in providing health education is considered very appropriate to convey health messages to the public, especially among adolescents.Purpose: To determine the effect of the knowledge of early marriage practices and the health impacts among adolescent in a health promotion programMethod: Quantitative research with